Thermal districts in Colombia: Developing a methodology to estimate the cooling potential demand. (September 2022) - Ríos-Ocampo, J.P.; Olaya, Y.; Osorio, A.; Henao, D.; Smith, R.; Arango-Aramburo, S.
Abstract: Thermal Districts have been presented globally as an efficient alternative to supply the demand for cooling and heating in urban areas. The development of thermal districts has been slow due to the uncertainty of demand and the lack of methods for estimating potential demands. However, the information needed for estimating district cooling potential is scarce in many cities, and the existing methodologies need to be adapted to specific conditions. This paper develops a methodology to estimate the potential for developing district cooling based on cities' climate and economic activities. The proposed methodology is applied in 13 Colombian metropolitan areas to identify potential clusters for district cooling according to the geographical distribution of buildings. The results show that the total potential demand for cooling in the 13 cities in Colombia is almost 650 MW. This paper concludes that demand for cooling that could be supplied with the implementation of tailor-made district cooling designed using the local economic characteristics of the cities through the 37 emerging clusters. Highlights: Introduction of methodology to estimate the potential demand for cooling. Potential demand for cooling estimated based on climate and economic activities. The methodology evaluates the potential demand for cooling in seven economic sectors. The 13 Colombian cities have potential demand for cooling of 650 MW. Colombian cities have the potential to install 37 cooling districts.